Bioética Latino-americana e afrocentricidade como práxis educativa de libertação: referenciais epistemológicos para a implementação da política pública de educação das relações étnico-raciais nos cursos de direito - Salles, Shayene Machado (2022)
From Latin American Bioethics and Afrocentricity, it is proposed to analyze the epistemological references, arising from such knowledge, for the constitution of an educational “praxis” of Liberation, based on the pillars of the Public-Racial Relations Education policy, to Law school. The goal is to find answers to the following questions: a) What are the possible contributions of both Bioethics and Afrocentricity, in their respective potentialities, to constitute a liberating educational “praxis” aimed to confront structural racism through the Education of Ethnic-Relations Racial in Law school?; b) How such knowledge (Bioethics and Afrocentricity) can contribute to the execution of the “National Plan for the Implementation of National Guidelines for the Education of Ethnic-Racial Relations” and the guideline of the “transversality of Education of Ethnic-Racial Relations in Law school”, established by art. 2º, §4º of Resolution n.º 5/2018 of the National Council of Education (legislation that establishes the National Curriculum Guidelines for the Undergraduate Law school)? Therefore, the public policy on Education of Ethnic-Racial Relations is correlated with both persistent issues in Bioethics (and with UNESCO Universal Declaration on Bioethics and Human Rights), rethinking principles and identifying the main theories and foundations arising from it, and the need and urgency to adopt an Afrocentric position to understand the world and Legal Education under the bias of counter-hegemonic references, which means, non-Western ones (bearing in mind the release from chains of oppression, deconstruction, and subjugation of Afrocentric epistemes, fostered by Eurocentrism). It is based on the dialectical conception of Law (and legal science) inspired by Roberto Lyra Filho, the Critical Theory of Law developed by Luís Alberto Warat, the conception of Law as Freedom from José Geraldo de Sousa Júnior, as well as the dialectical conception of Education adopted by Paulo Freire and systematized by Moacir Gadotti in “Pedagogy of Praxis”. In order to deepen the reflection on liberation in the educational field, we also refer to studies on age and, in particular, to the contributions of Enrique Dussel (to free oneself from the pressure of the world-system forged in the modern) and Aníbal Quijano (to free oneself from the colonialities of being, knowledge and power). The influence of such conceptions act as a relevant analytical substrate for the articulation of Latin American Bioethics (of Intervention) and Afrocentricity with Legal Higher Education, as well as for the root of their applicability, as epistemological references, to Ethnic-Racial Relations Education Policy. By identifying the epistemological contributions of Bioethics and Afrocentricity to Law school, which are called "bioethical assumptions and Afrocentric praxis-reflective" are identified as premises to be considered by a Legal Education conceived and understood as an effective practice of Freedom, proposing, in this way, the arrangement of an epistemology of critical analysis, potentially liberating (as anti-racist), insofar as it encourages a sensitive and committed look to ethnic-racial vulnerabilities in the context of Legal Higher Education